Determinants of the Implementation of the Education Unit Level Curriculum - Martina (CV. Era Digital Nusantara, 2024)
The purpose of this research is to see the leadership influence of the headmaster to the implementation of KTSP in SMA Sub Rayon 8 of Muara Enim, the District education officer and the influence of the competency of teachers on the implementation of KTSP in SMA Sub Rayon 8, Muara Enim District education. The variable includes the leadership of the school principal, teacher competence and implementation of KTSP. Analysis tool is a path analysis. Based on the analysis process shows the leadership of the school head either directly or indirectly affect the implementation of KTSP in SMA Sub Rayon 8, the Education Office of Muara Enim, and the competency of teachers directly affects the implementation of KTSP in SMA Sub Rayon 8 of Muara Enim District Education Officer. The conclusion shows that principal leadership and competence affect the implementation of KTSP.